Integrative transcriptomic, proteomic, and phosphoproteomic analysis on the defense response to Magnaporthe oryzae reveals different expression patterns at the molecular level of durably resistant rice cultivar Mowanggu - Peng, Weiye; Wang, Yunsheng; Zeng, Xuanning; Li, Wei; Song, Na; Liu, Jing; Wang, Bing; Dai, Liangying (Frontiers in Plant Science, 2023)
Rice blast, caused by Magnaporthe oryzae is one of the most destructive diseases of rice (Oryza sativa L.) in most rice-cultivated areas worldwide. Mowanggu (MWG) is a traditional landrace rice variety in Yunnan with broad-spectrum and durable blast resistance against rice blast fungus. However, the underlying disease-resistance mechanisms remain unknown. An integrative transcriptomic, proteomic, and phosphoproteomic analysis of MWG was performed after inoculation with M. oryzae in this study. The transcriptomic and proteomic results revealed that MWG was moderately correlated at the transcriptional and protein levels. Differentially expressed genes and proteins were up-regulated and significantly enriched in protein phosphorylation, peroxisome, plant-pathogen interactions, phenylpropanoid metabolism and phenylalanine biosynthesis pathways. The phosphoproteomic profile and phosphorylated-protein-interaction network revealed that the altered phosphoproteins were primarily associated with reactive oxygen species (ROS), glycolysis, MAPK signaling pathways, and amino acid biosynthesis. In addition, a series of physiological and biochemical parameters, including ROS, soluble sugars, soluble protein and callus accumulation and defense-related enzyme activities, were used to validate the possible blast resistance mechanisms of MWG. The integrative transcriptomic, proteomic, and phosphoproteomic analysis revealed the different expression patterns at the molecular level of the durably resistant rice cultivar MWG after inoculation with M. oryzae, which provides insight into the molecular mechanisms of rice blast resistance.